Criminal law protection of State symbols (Discourse of Law and Administration, 2026)
The article is aimed at providing an overview of the criminal law protection of the State symbols such as the emblem, banner, standard, ensign, flag or other State signs. The author emphasizes that the protection of these symbols is extremely important for the interests of the Republic of Poland. For centuries, the emblem, national colors, or Dabrowski’s Mazurka have expressed love for the homeland, united all Poles, both home and abroad, and conveyed the identity, honor, pride and dignity of the nation. For this reason, they should be legally protected, revered and respected. The State symbols can be used by all citizens, and therefore, the author hereof argues that in the legal space there has been formed a ‘constitutional right to use the State symbols’ which is subject to dualistic protection under the provisions of the Criminal Code and the Code of Offenses. The article presents the view that insulting the national anthem can be penalized on the basis of Article 133 of the Criminal Code, which is in line with the criminal law that appraises behaviors insulting either the Nation or the Republic. At the same time, the author noted that the best de lege ferenda solution would be to supplement the features referred to in the provision of Article 137 of the Criminal Code with the national anthem. This would allow avoiding doctrinal disputes over the possibility of applying interpretatio extensiva in the case of insulting Dabrowski’s Mazurka.
Keywords: national symbols; constitution; criminal code; code of offences; national anthem